Влияние технологических режимов операции у3-сварки на надёжность монтажных соединений - Невлюдов, И. Ш.; Андрусевич, А. А.; Стародубцев, Н. Г.; Невлюдова, В. В.; Малая, И. А. (ХНУРЕ, 2017)
A regression model of the process of mounting radio electronic products by means of ultrasonic micro-welding is developed. Its parameters are evaluated based on the results of the full factorial experiment of type 23, the optimum regimes are determined under which the maximum reliability of the mounting joints is ensured. As a criterion for evaluating the reliability of joints, their peel strength was chosen.
Keywords: надёжность монтажных соединений; технологический режим операции